Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1200/jco.2019.37.15_suppl.e14652
|View full text |Cite
|
Sign up to set email alerts
|

Effect on tumor growth by TGF-β1/COX-2 siRNA combination product (STP705) in a human cholangiocarcinoma (HuCCT-1) xenograft tumor model in nude mice.

Abstract: e14652 Background: Cholangiocarcinoma (CCA) is a hepatobiliary cancer and although there have been advances recently there is a need for additional treatment methods for patients. Over expressions of TGF-β1 and COX-2 have been reported to play key roles in tumorigenesis of CCA. We studied the effect of STP705 on the growth of HuCCT-1 xenograft tumors in nude mice. STP705 is a TGF-β1/COX-2 specific siRNA combination product formulated in Histidine-Lysine co-Polymer nanoparticle delivery system. Methods: HuCCT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Silencing expression of TGF-β1 and COX-2 to inhibit cell survival and induce tumor cell apoptosis Cutaneous squamous cell carcinoma skin cancer [196,197]…”
Section: Sirna-based Therapeutics For Cancer Treatmentmentioning
confidence: 99%
“…Silencing expression of TGF-β1 and COX-2 to inhibit cell survival and induce tumor cell apoptosis Cutaneous squamous cell carcinoma skin cancer [196,197]…”
Section: Sirna-based Therapeutics For Cancer Treatmentmentioning
confidence: 99%
“…48 STP705 is composed of siRNA oligonucleotides targeting TGFB1 and COX-2 mRNAs formulated with nanoparticles containing a unique histidine-lysine copolymer peptide. 49,50 Clinical trials for STP705 with intravenous or intralesional administration in patients with advanced/metastatic solid tumors in phase 1 or cutaneous squamous cell carcinoma (in situ) in phase 2 are currently underway.…”
Section: Antitumor Al S Mall Interfering Rna Smentioning
confidence: 99%
“…[246] Similarly, Sirnaomics uses their branched histidine-lysine polypeptide-siRNA NPs, of 150 nm, for the codelivery of siRNAs targeting transforming growth factor-beta (TGF-β) and cyclooxygenase-2 (COX-2) genes for the treatment of cutaneous squamous cell carcinoma in a phase I clinical trial. [248][249][250] These NPs will be delivered locally into the tumor. Preclinical studies have shown that the combined inhibition of TGF-β and COX-2 results in increased apoptosis, reduced tumor growth and rate of invasion in hepatobiliary cancer models.…”
Section: Polymeric Systems For Rna Anticancer Therapiesmentioning
confidence: 99%
“…Preclinical studies have shown that the combined inhibition of TGF-β and COX-2 results in increased apoptosis, reduced tumor growth and rate of invasion in hepatobiliary cancer models. [248] The use of CPPs has also been harnessed for an improved RNA delivery to the tumor cells. For example, an octa-arginine (R8) peptide linked to a targeting ligand (RGDS) at one end and two C18 lipid tails at the other were used to condense siRNA.…”
Section: Polymeric Systems For Rna Anticancer Therapiesmentioning
confidence: 99%